Study on the Compressive Properties and Factors of Recycled Mixture with High Content of Iron Tailings Sand - Yuanshuai Dong; Hong Zhang; Yun Hou; Peng Guo; Jialei Tian; Zhenyu Qian (Advances in Civil Engineering)
This paper focuses on the disposal of iron tailings sand (ITS) and recycled aggregate of inorganic (RAI) and proposed the “ITS plus RAI” solid waste treatment methods, which uses ITS and RAI as a new base course material to replace new aggregates by 100% to apply in the pavement renovation project of national and provincial roads in Linfen city, Shanxi Province. In this paper, the compressive strength characteristic of recycled mixture with different ratios is studied for the dual waste treatment methods, and the influence factors are analyzed by multiple regression analysis. Results show that the strength of the recycled mixture composed of a high content of ITS (the mass ratio to RAI exceeds 60 : 40) ups to 7 MPa, which can meet the pavement requirements of 7d unconfined compressive strength of inorganic stabilized base material under various traffic load conditions. The factors affecting the strength of recycled materials include the content of various components, while the particle size of iron tailings sand is the most significant influence factor. Therefore, the proportion of iron tailings sand in the recycled mixture can be further improved by screening coarse iron tailings sand so as to maximize the content of iron tailings sand, which will lead to an excellent engineering value.